A systematic review of the impact of adjusting input dynamic range (IDR), electrical threshold (T) level and rate of stimulation on speech perception ability in cochlear implant users. - Nunn, Terry B.; Jiang, Dan; Green, Tim; Boyle, Patrick J.; Vickers, Deborah A. (International Journal of Audiology, 2019)
Objective: To systematically review the evidence of how adjustments of the electrical threshold (T) level, input dynamic range (IDR) and electrical stimulation rate impact on speech perception for cochlear implant (CI) users. Design: Systematic review. Study sample: A search of two electronic data sources yielded 32 studies, which met the inclusion criteria. A quality assessment and two evidence-based practice (EBP) review rating schemes were used to grade studies. Results: Due to the heterogeneity of speech perception measures, CI device type and study design, comparisons were made by structured review. Conclusion: The quality of studies was found to be moderate to poor. Increasing T levels above behavioural threshold, or as a proportion of electrical dynamic range (EDR), has been demonstrated to improve perception of monosyllables in quiet and sentences in both quiet and in noise. Specific IIDR and IDR setting may improve perception of monosyllables in quiet and sentences in noise. However, no recommendation could be determined for setting rate of stimulation as speech perception varied significantly across rates examined. To optimise speech perception, a bespoke approach to parameter setting providing an individualised CI fitting is recommended; however, detail of how to optimise settings and the interactions between parameters is as yet unknown.